2008
DOI: 10.2133/dmpk.23.188
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Cytochrome P450 and Transcription Factors during In Vitro Differentiation of Mouse Embryonic Stem Cells into Hepatocytes

Abstract: Hepatocyte differentiation markers were expressed in the cells differentiated from mouse embryonic stem (ES) cells. In the differentiating ES cells, Cyp1a1 mRNA was highly expressed during the early to middle stage; Cyp2c29, Cyp2e1, Cyp3a11 and Cyp7a1 mRNAs were expressed only at the late stage; Cyp7b1 mRNA was expressed throughout all stages. Alpha-fetoprotein and albumin were co-expressed with Cyp3a and Cyp1a, respectively. Aryl hydrocarbon receptor, aryl hydrocarbon receptor nuclear translocator and glucoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…We have also found that PXR mRNA was expressed only at the late stage in differentiating mouse ES cells. 64) These findings suggest that the cells differentiated on Matrigel reduced-and Matrigel-coated plates demonstrate the characteristics of mature hepatocytes in the CYP3A8 gene expression response following RIF treatment, although cells differentiated on collagen I-coated plate were not sufficiently mature to induce CYP3A8 such as that in hepatoblasts.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…We have also found that PXR mRNA was expressed only at the late stage in differentiating mouse ES cells. 64) These findings suggest that the cells differentiated on Matrigel reduced-and Matrigel-coated plates demonstrate the characteristics of mature hepatocytes in the CYP3A8 gene expression response following RIF treatment, although cells differentiated on collagen I-coated plate were not sufficiently mature to induce CYP3A8 such as that in hepatoblasts.…”
Section: Discussionmentioning
confidence: 78%
“…6). We have previously found that aryl hydrocarbon receptor mRNA was detected in differentiating mouse ES cells throughout the culture period of 36 d. 64) These findings suggest that the enzyme induction process via aryl hydrocarbon receptor is already constructed in the hepatocytes-derived from cmES cells.…”
Section: Discussionmentioning
confidence: 81%
“…[15][16][17] Many of these methods involve a procedure to differentiate ESCs by EB formation and adhesion culture. EBs differentiate into three embryonic germ layers by suspended cell culture of ESCs, and these cells can then further differentiate into multiple cell types, including hepatocytes, in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…In an independent study, Cyp1a1 was shown to appear earliest — following which AHR, ARNT, and glucocorticoid receptor mRNAs as well — were detected in differentiating mouse ES cells throughout the culture period (Maezawa et al , 2008). The AHR-signaling pathway and sensitivity to PAH-caused toxicity were also described in human ES cells (Kee et al , 2010).…”
Section: Ahr and Cell-signaling Pathwaysmentioning
confidence: 99%